Perancangan E-Distribution Sebagai Media Promosi Dan Penjualan (Studi Kasus : A3 Cell) - Helen Anggraini; Romi Hendri; Rosita Cahaya (Universitas Mitra Indonesia, 2021)
AbstractOne way that is currently being widely used in an effort to support and increase company income is the use of internet facilities in the trade sector. By utilizing the internet as a medium to market products in large quantities and distribute them to online buyers, it is called E-Distribution. E-Distribution A3 Cell as a store engaged in selling internet quota and cellphone accessories currently does not own and use information media and technology in terms of information dissemination. So far, the system used is in the form of disseminating information from one consumer to another and is limited to the area around A3 Cell. A3 Cell relies on manual information, transactions in A3 Cell are still recorded in the Ledger, the search and report generation process takes a long time. Based on this, an E-distribution-based system is needed that can assist A3 Cell in providing updated product information and improving services to consumers without time and place restrictions. The results of the research that have been designed and tested show that the information system that has been created provides convenience in the sales process, data management of the distribution of goods as well as based on the results of the black box.